Experimental Study on the Evolution of Dynamic Pore Pressure and Unidirectional and Bidirectional Vibrations of Phosphogypsum - Kang, Fuqi; Wang, Guangjin; Liu, Wenlian; Zhao, Kui; Wang, Menglai; Li, Xiaoshuang; Zhong, Wen; Dong, Zhicheng (Frontiers in Earth Science, 2022)
Under seismic action, the stock of phosphogypsum (PG) affects the security risk significantly, so it is crucial to study the dynamic characteristics of PG. In this article, unidirectional and bidirectional vibration tests on typical PG in Yunnan under different consolidation-confining pressure and vibration conditions were carried out using a dynamic triaxial apparatus that can be used for bidirectional vibration. The results show that the pore pressure growth of PG under both unidirectional and bidirectional vibrations has obvious stages and can be fitted by the BiDoseResp function. The dynamic strength of PG does not increase monotonically with the increase in consolidation-confining pressure and dynamic stress under the same cyclic stress ratio (CSR) but varies under a specific critical condition. The dynamic strength of PG decreases significantly with the increase in CSR under unidirectional and bidirectional vibrations. The number of vibrations required for liquefaction by bidirectional vibrations is much larger than that by unidirectional vibrations under the same CSR conditions, and the specimens have significant softening characteristics after liquefaction by bidirectional vibrations. The study results can provide theoretical references for studying the dynamic stability of PG reservoirs under seismic action.